Relationship between parental perceptions, family income and support received with family quality of life in families with a child with an intellectual disability - Ferrer Vidal, Fina; Vilaseca Momplet, Rosa; Bersabé-Morán, Rosa María (Universidad de Salamanca, 2022)
Research has shown that families raising a child with intellectual disability (ID) face many challenges and need to implement adaptation strategies. Some authors suggest that positive parental perceptions and perceived control could reduce emotional impact and promote family wellbeing. Nevertheless, there are few studies about the relationship between parental perceptions and family quality of life (FQoL) in those families. In this study, we used data from a sample of 251 Spanish parents whose children have ID. Positive perceptions scale and control perceptions scale, Spanish FQoL scale under 18 years-old and a sociodemographic questionnaire were administered to those families. The results of bivariate analysis showed that some dimensions of positive perceptions were related to different areas of FQoL, for example, social inclusion and family accommodation. FQoL was associated with family income and support received.To predict the FQoL level, a multivariate linear regression analysis was conducted. Results indicated that FQoL scores can be predicted by a linear combination of positive perceptions and family income. Practical implications for promoting FQoL in these families are discussed.
Keywords: Minusválidos; Discapacidad intelectual; Calidad de vida familiar; Percepciones positivas; Control percibido; Ingresos familiares; Apoyo recibido